2021
DOI: 10.1002/mbo3.1185
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term exposure to synthetic flaxseed lignan LGM2605 alters gut microbiota in mice

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
(114 reference statements)
1
3
0
Order By: Relevance
“…As expected, the unabsorbed lignan was utilized as substrate by enterolactone-producing bacterial species, thus improving the gut microbiota diversity. These results were also observed in normal-fed mice models [44,45] and an in vitro pilot study [46]. Our results suggest that flaxseed lignan can modulate the composition of gut microbiota in the presence of paracetamol-induced liver injury.…”
Section: Discussionsupporting
confidence: 77%
“…As expected, the unabsorbed lignan was utilized as substrate by enterolactone-producing bacterial species, thus improving the gut microbiota diversity. These results were also observed in normal-fed mice models [44,45] and an in vitro pilot study [46]. Our results suggest that flaxseed lignan can modulate the composition of gut microbiota in the presence of paracetamol-induced liver injury.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies have shown that consuming FS or isolated FS components can alter the composition and function of the microbiota in humans [ 35 , 71 ] and rodent models [ 36 , 40 , 41 , 72 , 73 ], which may play a role in modulating the response to the LPS challenge. Therefore, we analyzed the fecal microbiota from mice following the three-week dietary intervention, prior to the SAL/LPS challenge, to assess the impact of diet on the baseline microbiota.…”
Section: Resultsmentioning
confidence: 99%
“…A few recent studies reported the modulating actions of lignans on gut microbial composition. Bader et al [36] revealed that flaxseed lignan secoisolariciresinol diglucoside altered 3 bacterial phyla and 22 genera after 10-day treatment in eightweek-old female C57BL/6 mice. Taibi et al [37] found that lignan-rich oilseeds could strongly influence the microbiota composition of younger and premenopausal females, and led to different enterolignan production in an in vitro fermentation experiment.…”
Section: Discussionmentioning
confidence: 99%